Optimalisasi Proses Penerimaan Santri Baru dengan Aplikasi Pendaftaran Berbasis Android pada Pondok Modern Daarul Istiqomah Air Gegas - Dimas Pramuja; Chandra Kirana (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
This study aimed to develop and evaluate an Android-based new student registration application to optimize administrative processes at Pondok Modern Daarul Istiqomah Air Gegas. The Research and Development (R&D) method was employed, utilizing a prototype approach consisting of five stages: needs analysis, design, iterative evaluation, system implementation, and black-box testing combined with user acceptance testing (UAT). Results confirmed that all core features including registration, form submission, data validation, and announcement of selection outcomes were fully functional and responsive. Featuring an intuitive interface and real-time database integration, the application effectively reduced administrative delays, data redundancy, and input errors commonly associated with manual systems. The study concludes that adopting Android mobile technology significantly enhances the efficiency, accuracy, and transparency of the new student admission process, while supporting the digital transformation of Islamic boarding schools toward more adaptive and professional management.